Social Inequality and Social Mobility: The Construed Diversity of Ethiopian Female Labor Migrants in Djibouti - Eresso, Meron Zeleke (African Human Mobility Review, 2021)
Discussions about female labor migrants from the Horn of Africa are oftenloaded with accounts describing them as a homogenized group of destitutepeople on the move. Such trends of homogenization often hide the diverse socialclasses within these groups and the differential access co-nationals have acrosssuch social classes. Moreover, such discourses conceal the differences inmigrants’ migration trajectories and related variances in their overallintegration processes. This paper accentuates the heterogeneity of the socialclasses of Ethiopian female migrants and argues that the term Ethiopian femalemigrant is a parasol that often obscures the diverse and highly stratified migrantgroup. By going beyond this dominant trend of homogenization, this studyaddresses how differential access to economic resources, different socialcharacteristics of migrants, and migrants’ settlement patterns impact migrants’networks and their status within the larger Ethiopian female migrant group.